VALUASI NILAI EKONOMI KARBON MANGROVE DI KAWASAN MANDEH KECAMATAN KOTO XII TARUSAN KABUPATEN PESISIR SELATAN - Syafruddin, Yudha Saktian; Yurike, Yurike (Program Studi Pendidikan Geografi STKIP PGRI Sumatera Barat, 2020)
This research discusses the function of mangrove ecosystem in the area of Mandeh Koto XII Tarusan South Coast district. Mangrove is a plant that is able to survive in high salinity condition. Mangrove ecosystems that have a high ecological and economic value are equally good with the ability of Carbon Sink four times higher than other primary forests. The absorption of mangrove carbon has a high economic value as a global carbon emissions absorber, so it is necessary to see the valuation of economic value on the existence of mangrove so that we can preserve and protect the existence of mangrove forest for joint prosperity.